Assessment of the AHRQ patient safety initiative : focus on implementation and dissemination evaluation report III (2004-2005) - Farley, Donna (Technical report (Rand Corporation), 2007)
RAND has contracted with the Agency for Healthcare Research and Quality (AHRQ) to perform a longitudinal evaluation of the full scope of AHRQ's patient safety activities and to provide regular feedback to support the continuing improvement of the initiative over a four-year evaluation period. This interim report presents an update on the work RAND has performed during FY 2007 for the practice diffusion assessment. The assessment encompasses five specific analytic components: (1) development of a survey questionnaire to use for assessing adoption of the safe practices endorsed by the National Quality Foundation, (2) community studies of patient safety practice adoption and related activities, (3) continued analysis of trends in patient outcomes related to safety, (4) lessons from hospitals' use of patient safety tools developed by AHRQ, and (5) a second fielding of the hospital adverse event reporting system survey.